2009
DOI: 10.5012/bkcs.2009.30.7.1470
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photochemistry of Methyl Iodide on Ice Film Grown on Cu(111)

Abstract: Thermal and photochemistry of methyl iodide (CH3I) adsorbed on D2O ice film on Cu(111) at 100 K were studied using temperature-programmed desorption (TPD) time-of-flight mass spectrometry (TOF-MS), X-ray and ultraviolet photoelectron spectroscopies. On the basis of TPD, multilayer and monolayer CH3I molecules desorb from D2O ice layer at 120 and 130 K, respectively. Photo-irradiation at 100 K exhibits dramatic changes in the TPD and I 3d5/2 XPS of CH3I on ice film, due to a dramatic dissociation of CH3I. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…18,19 The discovery of primarily methyl iodide (CH 3 I) as potential sources of reactive halogen species during ozone depletion processes 7,8 have motivated investigations of photodissociation of CH 3 I adsorbed on ice. 9,10,20 There have been extensive experimental and theoretical studies on the photodissociation of CH 3 I in the gas phase 21−25 or adsorbed on ice surfaces. 20 In gas phase, 21−25 decomposition along C−I bond (σ*←n) leads to different photoproducts including I 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The discovery of primarily methyl iodide (CH 3 I) as potential sources of reactive halogen species during ozone depletion processes 7,8 have motivated investigations of photodissociation of CH 3 I adsorbed on ice. 9,10,20 There have been extensive experimental and theoretical studies on the photodissociation of CH 3 I in the gas phase 21−25 or adsorbed on ice surfaces. 20 In gas phase, 21−25 decomposition along C−I bond (σ*←n) leads to different photoproducts including I 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Iodine compounds are naturally released mainly from the oceans either by marine metabolisms (i.e., phytoplankton and micro- and macro-algae) or, in the case of inorganic iodine species (HOI and I 2 ), resulting from the reaction between O 3 and iodide in seawater. Terrestrial sources of iodine species from arid regions are much less important than marine sources, but have been identified as significant O 3 sinks . The measurements performed during field campaigns showed that photochemical processes occurring within the snowpack may alter the atmospheric composition including the iodocarbon content. , The discovery of primarily methyl iodide (CH 3 I) as potential sources of reactive halogen species during ozone depletion processes , have motivated investigations of photodissociation of CH 3 I adsorbed on ice. ,, There have been extensive experimental and theoretical studies on the photodissociation of CH 3 I in the gas phase or adsorbed on ice surfaces . In gas phase, decomposition along C–I bond (σ*← n ) leads to different photoproducts including I 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The interactions of adsorbed organic molecules on ice have been investigated using techniques such as temperature-programmed desorption (TPD), 5-7 electron-stimulated desorption, 8 X-ray photoelectron spectroscopy, 9,10 and reflection absorption infrared absorption spectroscopy. 11,12 These studies show that adsorption, diffusion, and desorption of organic molecules depend largely on the morphology of the ice substrate.…”
Section: Introductionmentioning
confidence: 99%